Even high normal blood pressure affects live birth rate in women undergoing fresh embryo transfer. Issue 11 (19th September 2022) - Chen, Huijun; Zhang, Xiaoli; Cai, Sufen; Li, Jian; Tang, Sha; Hocher, Carl-Friedrich; Rösing, Benjamin; Hu, Liang; Lin, Ge; Gong, Fei; Krämer, Bernhard K; Hocher, Berthold
Abstract: STUDY QUESTION: Do differences in blood pressure within the normal range have any impacts on the live birth rate (primary outcome) or biochemical pregnancy rate (beta-hCG positivity), clinical pregnancy rate (heart beating in ultrasound), abortion rate and ectopic pregnancy rate (secondary outcomes) of fresh embryo transfer in women undergoing their IVF/ICSI treatment? SUMMARY ANSWER: Even rather small differences in baseline blood pressure in women with normal blood pressure according to current guidelines undergoing fresh embryo transfer after IVF/ICSI affects substantially the live birth rate. WHAT IS KNOWN ALREADY: Pre-pregnancy hypertension is a well-known risk factor for adverse pregnancy events such as preeclampsia, fetal growth restriction, placental abruption and adverse neonatal events. It is likewise well known that hypertension during pregnancy in women undergoing ART is associated with adverse pregnancy outcomes. However, whether blood pressure at the high end of the normal range has an impact on ART is unknown. STUDY DESIGN, SIZE, DURATION: It is a prospective observational cohort study based on a single IVF center between January 2017 and December 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: Two thousand four hundred and eighteen women with normal blood pressure undergoing fresh embryo transfer after IVF/ICSI at the Reproductive and Genetic Hospital of CITIC-Xiangya were enrolled in this study. MAIN RESULTS AND THE ROLE OF CHANCE: Blood pressure was measured at the first visit when women consulted the IVF center due to infertility. In women with a successful pregnancy outcome (1487 live births out of 2418 women undergoing fresh embryo transfer after IVF/ICSI), systolic blood pressure (SBP) (114.1 ± 9.48 mmHg versus 115.4 ± 9.8 mmHg, P  = 0.001) and diastolic blood pressure (DBP) (74.5 ± 7.5 mmHg versus 75.3 ± 7.34 mmHg, P  = 0.006) were lower than in those who did not achieve live births. Multivariate logistic regression analysis revealed that SBP (OR: 0.987, 95% CI: 0.979–0.996, P  = 0.004) and DBP (OR: 0.986, 95% CI: 0.975–0.998, P  = 0.016) were negatively associated with live birth. Similarly, SBP was significantly negatively related to clinical pregnancy rate (OR: 0.990, 95% CI: 0.981–0.999, P  = 0.033), while for DBP the association was not statistically significant (OR: 0.994, 95% CI: 0.982–1.006, P  = 0.343). However, both SBP and DBP were positively associated with miscarriage OR: 1.021 (95% CI: 1.004–1.037, P  = 0.013) and OR: 1.027 (95% CI: 1.005–1.049, P  = 0.014), respectively. Both SBP and DBP were unrelated to biochemical pregnancy (hCG positivity), implantation and ectopic pregnancy rate. LIMITATIONS, REASONS FOR CAUTION: Whether lowering blood pressure before initiating ART treatment in women with SBP or DBP higher than the thresholds defined in our study will confer a benefit is unknown. Also, we cannot exclude bias due to different ethnicities. Moreover, participants in our study only received fresh embryo transfer, whether the results could apply to frozen embryo transfer is unclear. WIDER IMPLICATIONS OF THE FINDINGS: Our study challenges the current blood pressure goals in women undergoing fresh embryo transfer after IVF/ICSI. Further studies are needed to figure out the mechanism and effective approach to increase IVF/ICSI pregnancy outcomes. STUDY FUNDING/COMPETING INTEREST(S): Hunan Provincial Grant for Innovative Province Construction (2019SK4012). The authors declare that there were no conflicts of interest in this study. TRIAL REGISTRATION NUMBER: N/A.